1981
DOI: 10.1095/biolreprod25.4.777
|View full text |Cite
|
Sign up to set email alerts
|

Further Effects of Nonsteroidal Anti-inflammatory Compounds on Blastocyst Hatching in vitro and Implantation Rates in the Mouse1

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 17 publications
3
18
0
Order By: Relevance
“…It was confirmed for the first time that morphological changes from 2-cell embryos until blastocoel formation and the time needed for such development did not differ between parthenogenetic and fertilized embryos. In the fertilized embryos of the present study, it was also confirmed that morphological changes until blastocoel formation and the diameters of the blastocyst stage are consistent with those of previous reports with fertilized mouse embryos [14][15][16][17].…”
Section: Discussionsupporting
confidence: 92%
“…It was confirmed for the first time that morphological changes from 2-cell embryos until blastocoel formation and the time needed for such development did not differ between parthenogenetic and fertilized embryos. In the fertilized embryos of the present study, it was also confirmed that morphological changes until blastocoel formation and the diameters of the blastocyst stage are consistent with those of previous reports with fertilized mouse embryos [14][15][16][17].…”
Section: Discussionsupporting
confidence: 92%
“…It was also determined that the number of weak contractions until 32 h after blastocoel formation was similar in zona-intact and zona-free mouse blastocysts, whereas strong contractions were observed more in zona-free blastocysts (Table 5) [33]. Mouse blastocysts treated with indomethacin (IM), which is an inhibitor of the biosynthesis of prostaglandins (PGs) related to blastocyst hatching [34,35], had the same number of weak contractions as that observed in non-treated blastocysts, but the number of strong contractions was larger and the hatching rate was lower in the IM-treated blastocysts [36]. When blastocysts were treated with PGF2α or PGE2, in combination with IM, the hatching rate and the number of weak and strong contractions were comparable to those observed in non-treated blastocysts (Table 6) [36].…”
Section: Role Of Contractions In Blastocyst Hatchingmentioning
confidence: 99%
“…Blastocoelic expansion has been reported as prostaglandin-dependent since several nonsteroidal anti-inflammatory drugs, including indomethacin and meclofenamic acid, and inhibitory analogues of prostaglandins E and F-2rx limit expansion and reduce hatching (Biggers, Leonov, Baskar & Fried, 1978;Baskar et ai, 1981;Hurst & MacFarlane, 1981). Weakening or lysis of the zona pellucida is believed to be due to a zona lysin of uterine origin which may also have a role in initiating implantation (McLaren, 1970;Mintz, 1972;Hoversland & Weitlauf, 1981, 1982.…”
Section: Introductionmentioning
confidence: 99%